1995
DOI: 10.1177/00220345950740080301
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Protein Deficiency and Diet Consistency on the Parotid Gland and Parotid Saliva of Rats

Abstract: Protein deficiency results in an increased susceptibility to dental caries, suggesting that oral host-defense properties are compromised. An important component of oral host defense is salivary gland function, which is affected by both protein deficiency and diet consistency. This study describes the effects on rat parotid gland growth and secretory function induced by feeding rats diets of normal (20%) or moderately low (7%) protein content, provided in either a powdered or solid form. In addition, since prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Dietary zinc has been considered necessary for the proper development and growth of mammals including humans (Burch & Sallivan 1975). Combined protein deficiency along with zinc might stimulate salivary gland functions that in turn affect the liver zinc contents (Johnson et al 1995). Protein deficiency leads to depletion of liver zinc contents (Gonzalez et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Dietary zinc has been considered necessary for the proper development and growth of mammals including humans (Burch & Sallivan 1975). Combined protein deficiency along with zinc might stimulate salivary gland functions that in turn affect the liver zinc contents (Johnson et al 1995). Protein deficiency leads to depletion of liver zinc contents (Gonzalez et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The present results concerning the RBD agree with those reported by other investigators (6,(21)(22)(23) who reported that malnutrition can cause a rise in the prevalence of caries. Various factors may have contributed to the high prevalence of caries found with the use of the RBD, such as enamel malformation due to episodes of malnutrition (24)(25)(26)(27)(28)(29), affected salivary glands (17,23,30,31), and the composition of the diet itself which, in addition to being deficient in proteins, vitamins and minerals, is rich in carbohydrates (10). When comparing the results for different times of animal feeding, we observed that the animals fed 30 days (1A and 2A) presented caries with less prevalence than the animals fed 60 days (1B, 2B), except for groups 3A and 3B.…”
Section: Resultsmentioning
confidence: 99%
“…To compare equal protein loads it is necessary to determine the protein concentration of the samples in a reliable manner. The protein concentration of rat parotid saliva has been determined using the Lowry [9±14, 18,22,35,36], the Arneberg [20,31] and the Bradford [7,8] protein assays. The Arneberg method is more reliable than the Lowry assay for the detection of PRP [31] and the ratio of the respective protein concentration values (Lowry:Arneberg) has been recommended as an index of the proportion of PRP in the saliva [20].…”
Section: Discussionmentioning
confidence: 99%
“…4 1378 [22] are indicated to the right hand side of pattern A: 1, basic proline-rich protein; 2, amylase; 3, SP-1 (basic proline-rich protein); 4, acidic proline-rich protein; 5, deoxyribonuclease; 6, acidic epididymal glycoprotein; 7, SP-3 (basic proline-rich protein); 8, parotid secretory protein; 9, common salivary protein 1a; and 10, common salivary protein 1b. Arrowheads indicate the major protein spots corresponding to these M r positions.…”
Section: -Dementioning
confidence: 99%
See 1 more Smart Citation